2018
DOI: 10.1166/jnn.2018.15336
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural, Optical and Dielectric Properties of Nanostructured 0–3 PZT/PVDF Composite Films

Abstract: Nanostructured PbZr0.52Ti0.48O3 (PZT) powder was synthesized at 500 °C-800 °C using sol-gel route. X-ray diffraction and Rietveld analysis confirmed the formation of perovskite structure. The sample heat treated at 800 °C alone showed the formation of morphotropic phase boundary with coexistence of tetragonal and rhombohedral phase. The PZT powder and PVDF were used in 0-3 connectivity to form the PZT/PVDF composite film using solvent casting method. The composite films containing 10%, 50%, 70% and 80% volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…However, the intensity of the diffraction peak at 2 θ = 21.4° reflects the superposition of the (110) and (200). [ 42 ] A strongly visible crystalline plane (200) indicated that the composite's polar phase was confirmed. These results demonstrated that only 0.05 wt% of PZT/GO is required to nucleate the TT confirmation of the β‐phase in all PVDF‐HFP chains.…”
Section: Resultsmentioning
confidence: 99%
“…However, the intensity of the diffraction peak at 2 θ = 21.4° reflects the superposition of the (110) and (200). [ 42 ] A strongly visible crystalline plane (200) indicated that the composite's polar phase was confirmed. These results demonstrated that only 0.05 wt% of PZT/GO is required to nucleate the TT confirmation of the β‐phase in all PVDF‐HFP chains.…”
Section: Resultsmentioning
confidence: 99%
“…Both the PVDF and nanocomposites are stable up to 420 °C, and after this temperature, there is sudden loss of weight because of cleavage in polymer chains, arising from thermal degradation. 28 However, there is no change of degradation temperature in the composite as compared to pure PVDF. This is to mention that BT does not lose any weight up to 700 °C other than meager quantity of adsorbed water.…”
Section: Resultsmentioning
confidence: 93%
“…There is no weight loss around 100 °C in the nanocomposites, which shows their hydrophobic nature. Both the PVDF and nanocomposites are stable up to 420 °C, and after this temperature, there is sudden loss of weight because of cleavage in polymer chains, arising from thermal degradation . However, there is no change of degradation temperature in the composite as compared to pure PVDF.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22] Currently, 0-3 PVDF/lead zirconate titanate (PZT) piezoelectric composites are mostly employed in research because of their superior properties, such as high permittivity and piezoelectric coefficient. [23][24][25][26][27][28] However, they are affected by many problems such as aggregation of fillers 29 and poor compatibility between the PVDF matrix and PZT fillers. To solve these problems, the surface modification of PZT particles to increase their dispersion and compatibility with PVDF has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%